Defining and Negotiating the Social Value of Research in Public Health Facilities: Perceptions of Stakeholders in a Research‐Active Province of South Africa. (February 2017) - Lutge, Elizabeth; Slack, Catherine; Wassenaar, Douglas
Abstract: This article reports on qualitative research conducted in KwaZulu‐Natal, South Africa, among researchers and gate‐keepers of health facilities in the province. Results suggest disparate but not irreconcilable perceptions of the social value of research in provincial health facilities. This study found that researchers tended to emphasize the contribution of research to the generation of knowledge and to the health of future patients while gate‐keepers of health facilities tended to emphasize its contribution to the healthcare system and to current patients. Furthermore, relations between research stakeholders were perceived to be somewhat fragile, making it difficult for stakeholders to achieve consensus about the social value of research, as well as on ways to maximize value. Interventions to negotiate a shared perspective on the social value of research would appear to be warranted, and the findings of this study suggest some focus areas for such intervention.